Penyusunan Skala Prioritas Saluran Drainase Di Tiga Kecamatan - Zahra, Vivi Widia; Sujatmoko, Bambang; Hendri, Andy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The inundation area is an area that inundated by water in case of the drainage channel cannot accommodate the flow of discharge, which causes the material losses and disturb the community activities. However, to solve the problem of flooding in Pekanbaru can not be done thoroughly because of the limited funds. Therefore, it is necessary to prepare the priority scale of channel rehabilitation drainage in Pekanbaru. The preparation of priority scale of drainage channel is done by using Analytic Network Process (ANP) method and assisted with Super Decisions software. The preparation of the priority scale refers to the rules minister of public works number: 12 / PRT / M / 2014. The results show there are 10 locations which ranked by the priority scale from the highest to the lowest which is the highest priority is the Tanjung Datuk street of Limapuluh subdistrict and the lowest is kota baru street of Senapelan subdistrict.Keywords : Analytic Network Process, Inundation, Drainage channel, Priority scale